Australia : 2010 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The impact of the global crisis was milder in Australia than in other advanced economies owing to strong demand from Asia and decisive policy responses. Australian banks were resilient to the global crisis, and the labor market was flexible in the face of the shock. The exit from fiscal stimulus is appropriate as is the recent review of the tax system. Banks could adopt riskier strategies and require vigilance. The exchange rate is overvalued but will dissipate as interest rates in other advanced economies eventually normalize.